MODERN APPROACHES TO REDUCING COMPLICATIONS IN GROIN HERNIA SURGERY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Groin hernia repair is one of the most common surgical procedures worldwide, yet postoperative complications such as chronic pain, recurrence, and infection remain significant challenges. Background: Groin hernia repair is among the most performed surgeries globally, yet complications such as chronic pain (10-12%) and recurrence (1-5%) remain prevalent. Methods: This review evaluates modern solutions, including laparoscopic/robotic techniques, lightweight meshes, and ERAS protocols, through a synthesis of recent clinical evidence. Results: Minimally invasive approaches reduce chronic pain to 5% (vs. 12% in open repair) and accelerate recovery (7 vs. 14 days to return to work). Lightweight meshes decrease mesh-related discomfort by 55%, while ERAS protocols shorten hospitalization to